Health literacy of patients on oral anticoagulation treatment- individual and social determinants and effect on health and treatment outcomes - Ana Cristina Cabellos-García; Antonio Martínez-Sabater; Miguel Ángel Díaz-Herrera; Vicente Gea-Caballero; Enrique Castro-Sánchez (BMC, 2021)
Abstract Background Assessment health literacy in people with cardiovascular health problems would facilitate the development of appropriate health strategies for the care and reduction of complications associated with oral anticoagulation therapy. Aim: To evaluate the relationship between health literacy and health and treatment outcomes (concordance with oral anticoagulants, Normalized Ratio control and occurrence of complications) in patients with cardiovascular pathology. Methods Observational, analytic and cross-sectional study carried out on 252 patients with cardiovascular pathology (atrial fibrillation, flutter or valve prosthesis), aged 50-85 years, accessing primary care services in Valencia (Spain) in 2018-2019. Variables referring to anticoagulant treatment with vitamin K antagonists (years of treatment, adequate control, polypharmacy and occurrence of complications, among others) and health literacy (Health Literacy Questionnaire) were analysed. Results All dimensions of health literacy were significantly related to the level of education (p < 0.02), social class (p < 0.02), an adequate control of acenocoumarol (p < 0.001), frequentation of health services (p < 0.001), information by patients to health professionals about anticoagulant treatment (p < 0.03), emergency care visits (p < 0.001) and unscheduled hospital admissions (p < 0.001). Conclusion Health literacy has a relevant influence on the adequate self-management of anticoagulation treatment and the frequency of complications. The different dimensions that comprise health literacy play an important role, but the "social health support" dimension seems to be essential for such optimal self-management. Trial registration ACC-ACE-2016-01. Registration date: December 2015.